1984
DOI: 10.4319/lo.1984.29.5.0972
|View full text |Cite
|
Sign up to set email alerts
|

Responses of phytoplankton to experimental nutrient enrichment in an Amazon floodplain lake1

Abstract: Natural algal populations in 4-, lo-, and 800-liter enclosures were fertilized to ascertain to what extent ammonium, nitrate, or phosphate enrichment changed phytoplankton abundance and physiology in an Amazon floodplain lake (Lake Calado). When water was rising and was between 8 and 11 m (March-May 1982), algal abundance ranged from 13-24 pg Chl a.liter-l and epilimnetic NH,+, N03-, and POa3-concentrations were usually ~0.3 HM. Chlorophyll increased over the control by 60-265% in the P treatment, 5-40% in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0

Year Published

1988
1988
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(44 citation statements)
references
References 13 publications
0
44
0
Order By: Relevance
“…Although SRP was not drawn down in river water after passage through the Apure floodplain, DIN decreased strongly, suggesting higher demand for dissolved N by floodplain biota. Evidence of N deficiency has been obtained in lakes of the mainstem Amazon River (Devol et al 1984;Forsberg 1984;Setaro and Melack 1984), but those studies did not reveal the nutrient status of phytoplankton when the external supply of labile N and P was high and dominated by inflows of river water.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although SRP was not drawn down in river water after passage through the Apure floodplain, DIN decreased strongly, suggesting higher demand for dissolved N by floodplain biota. Evidence of N deficiency has been obtained in lakes of the mainstem Amazon River (Devol et al 1984;Forsberg 1984;Setaro and Melack 1984), but those studies did not reveal the nutrient status of phytoplankton when the external supply of labile N and P was high and dominated by inflows of river water.…”
Section: Discussionmentioning
confidence: 99%
“…Phytoplankton biomass generally ranges between 10 and 25 pg liter-l in the lake (Fisher et al 1991;Smith-Morrill 1987;Setaro and Melack 1984). However, in 19 89, chlorophyll concentrations declined steadily from 20-30 yg liter-l in April to well below 3 pg liter-l during the throughflow phase, rising again only on the falling limb of the hydrograph.…”
Section: Discussionmentioning
confidence: 99%
“…There are also many leguminous macrophytes on the Amazon floodplain that actively fix N (Salati et al 1982;Victoria unpubl. data), and there are reports of N-fixing, blue-green bacteria in some Amazon floodplain lakes (Schmidt 1973a;Setaro and Melack 1984;B. Forsberg unpubl.…”
Section: Though the Concentrations Of Both Srp Andmentioning
confidence: 99%
“…These lakes can be highly productive (Schmidt 19733;Fisher and Parsley 1979;Devol et al 1984b) Araujo-Lima et al 1986). As in temperate systems, nitrogen and phosphorus appear to be the principal nutrients limiting primary producers in these floodplain lakes (Zaret et al 198 1;Forsberg 1984;Devol et al 1984a; Setaro and Melack 1984;Pinheiro 1985) and are likely to play key roles in maintaining lacustrine productivity. However, the factors controlling the concentrations of N and P in these lakes are poorly understood.…”
mentioning
confidence: 99%
“…This characteristic is even more pronounced in ecosystems with low nutrient concentrations, such as the clear and black water Amazonian ecosystems (Sioli, 1984;Setaro & Melack, 1984;Esteves et al, 1990). The participation of aquatic macrophytes in nutrient cycling has been verified by many authors (e.g., Granéli & Solander, 1988;Nogueira et al, 1996), who have demonstrated the role of this community in the absorption of nutrients from the sediment as well as their liberation in the water column.…”
Section: Introductionmentioning
confidence: 99%